MENAKAR IDEALITAS LAPANGAN PUPUTAN SEBAGAI RUANG PUBLIK MASYARAKAT KOTA DENPASAR - Wahyu Budi Nugroho; Gede Kamajaya (Program Magister Ilmu Politik, Universitas Diponegoro, 2019)
This research discusses public space in Denpasar, Bali, focusing on Lapangan Puputan. Theoretically, public space has three functions, namely recreational, social interaction and political aspect. Using Habermas's theory on public space, this article found Lapangan Puputan fulfils three functions of public space. Yet, there is a lack of society's understanding on the function of public space, in which the space is functioned more for economic activity. They also refuse if Lapangan Puputan is used for political activity.